Reducing Splitting of ‘Murcott’ Tangor Fruit (Citrus reticulate × Citrus sinensis) through Foliar Application of Forchlorfenuron (CPPU) - Yi-Lu Jiang; Pai-Tsang Chang (Horticulturae)
The effect of N-(2-chloro-4-pyridyl)-N′-phenylurea (CPPU) on fruit splitting of ‘Murcott’ tangor fruit (Citrus reticulate × Citrus sinensis) was analyzed throughout two successive seasons during 2020 and 2021. ‘Murcott’ trees were treated with various concentrations of CPPU, 1.0, 5.0, and 10.0 mg·L−1, which significantly reduced the splitting of fruit compared with the control fruit and the gibberellic acid (GA3)-treated fruit (20.0 mg·L−1). The fruit treated with 5.0 mg·L−1 CPPU exhibited higher levels of fruit weight, longitudinal diameter, transverse diameter, peel strength, and peel thickness compared to the control fruit. In addition, the tree sprayed with 5.0 mg·L−1 CPPU had the greatest number of cellular layers and cells at the stylar end calculated in fruit. However, there were no other fruit quality characteristics significantly affected by CPPU and GA3 treatments.